Modification of Fast-Growing Wood into Magnetic Wood with Impregnation Method Using Fe3O4 Nanoparticles - Esti Prihatini; Irma Wahyuningtyas; Istie Sekartining Rahayu; Rohmat Ismail (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Fast-growing wood is rarely used by the community because of its low quality. This study aimed to modify the sengon (Falcataria moluccana) and jabon (Anthocephalus cadamba) into magnetic wood so they have new functions. In this study, the modification process was performed by impregnating five-level concentrations of Fe3O4 nanoparticles dissolved in two different dispersants, namely water and a mixture of furfuryl alcohol and water. The impregnation process is initiated by a vacuum of -0.5 bar, followed by a pressure of 1 bar for 120 min. The addition of furfuryl alcohol to the impregnation solution significantly increased the physical properties of magnetic wood. The presence of Fe3O4 in wood is also proven by the Fe-O groups observed from the FTIR spectrum analysis. The magnetic field strength also increased as the concentration level of Fe3O4 increased. Based on the results of this research, the best treatment was obtained on magnetic wood of sengon and jabon with furfuryl alcohol and Fe3O4 nanoparticles concentration of 7.5%. Keywords: Fast-growing wood, impregnation, magnetic wood, nanoparticles, nano Fe3O4